Mechanism of Neonatal Intestinal Injury Induced by Hyperoxia Therapy - Tian-Ming Li; Dong-Yan Liu (Journal of Immunology Research)
High concentration oxygen is widely used in the treatment of neonates, which has a significant effect on improving blood oxygen concentration in neonates with respiratory distress. The adverse effects of hyperoxia therapy on the lung, retina, and neurodevelopment of newborns have been extensively studied, but less attention has been paid to intestinal damage caused by hyperoxia therapy. In this review, we focus on the physical, immune, and microorganism barriers of the intestinal tract and discuss neonatal intestinal tract damage caused by hyperoxia therapy and analyze the molecular mechanism of intestinal damage caused by hyperoxia in combination with necrotizing enterocolitis.